Notes on threatened plants of León (Spain), III - del Egido, Fermín; Fernández Cañedo, María; Bariego, Patricio; Puente, Emilio; López Pacheco, María José (Lazaroa, 2017)
In this paper we provide new records and comments about 19 protected and/or threatened vascular plants in the province of León.